2018
DOI: 10.1111/jvh.13022
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplant listing for hepatitis C‐associated cirrhosis and hepatocellular carcinoma has fallen in the United Kingdom since the introduction of direct‐acting antiviral therapy

Abstract: Summary Following the introduction of direct‐acting antivirals (DAA), there have been reports of declining incidence of hepatitis C (HCV)‐related liver disease as a liver transplantation indication. In this study, we assessed the impact of DAA on liver transplant indications in the UK and waiting list outcomes for patients with HCV. We assessed UK adult elective liver transplant registrants between 2006 and 2017. The aetiology of liver disease at registration was reclassified using an accepted hierarchical sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 12 publications
4
15
0
1
Order By: Relevance
“…Through linked data, we identified a decline in HCV-associated liver transplant rates after 2014, consistent with unlinked published data for England [2,8] and internationally [9-11]. A separate study within the UK [8], using unlinked data, reported registered transplants for patients with HCV-related cirrhosis fell from 10.5% in 2013 to 4.7% in 2016.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Through linked data, we identified a decline in HCV-associated liver transplant rates after 2014, consistent with unlinked published data for England [2,8] and internationally [9-11]. A separate study within the UK [8], using unlinked data, reported registered transplants for patients with HCV-related cirrhosis fell from 10.5% in 2013 to 4.7% in 2016.…”
Section: Discussionsupporting
confidence: 80%
“…Since the expansion of treatment with DAAs in England, a 43% drop in the number of liver transplant registrations has been recorded for individuals with post-HCV cirrhosis [2]. Vaziri et al reported that the proportion of liver transplants attributed to HCV-associated cirrhosis fell from 10.5% to 4.7% between 2013 and 2016 and the proportion of liver transplants for cancer-associated HCV fell from 46.4% to 33.7% over the same period [8]. Similar results have been found in Italy, the United States (US) and Argentina [9-11].…”
Section: Introductionmentioning
confidence: 99%
“…A fall in ESLD and HCC incidence was expected, as progression to liver disease is prevented by successful HCV treatment, the rates of which have increased since the phasing out of interferon‐based treatments and the introduction of DAAs in 2014, and as Operational Delivery Networks (who are responsible for local treatment decisions for persons with HCV) have increased case finding to achieve treatment quotas. Similar declines have been observed in liver transplant rates in persons with HCV, and although not significant a reduction in liver disease mortality rates has also been observed . The lag in HCC admission incidence reduction, when compared to ESLD admission incidence, could be due to the former having more advanced liver disease.…”
Section: Discussionsupporting
confidence: 58%
“…As the UK has signed up to the WHO global strategy for elimination of viral hepatitis as a significant public health threat by 2030 and the National Health Service (NHS) is ramping up HCV treatment rates nationally, it is important to benchmark the burden of HCV‐associated disease in the pre‐DAA era and monitor the evolution of HCV‐associated liver disease following their introduction. While there has been some work to show the positive initial impact of DAAs on HCV‐associated burden of disease in the UK, the incidence of ESLD and HCC, based on NHS Hospital Episode Statistics (HES) inpatient care data, has continued to increase post‐DAA introduction . However, it is unknown whether this increase is a true reflection of the current burden or influenced by changes in reporting of HCV within HES, as this methodology relies on HCV diagnosis been recorded on a patient's record.…”
Section: Introductionmentioning
confidence: 99%
“…One-half of the HCC cases among the three-fold increase in HCC incidence between 1975 and 2007 in the US can be attributed to the aging chronic HCV population. 2 Although there are indications that DAAs may slow progression to HCC, 20,21 there remains a vast population of HCC patients that could potentially benefit from treatment of their chronic HCV infections.…”
Section: Discussionmentioning
confidence: 99%